Determination of benzoic acid and sorbic acid in foodstuffs by high performance liquid chromatography with UV detection - Costa, João (2018)
Introduction: In recent decades, there has been a change in the dietary pattern of the population towards an increase in consumption of more industrialized foods. With this, food industry has faced many challenges on maintaining the quality and nutritional value of the products and at the same time increasing the shelf life. Benzoic Acid (BA) and Sorbic Acid (SA), and its salts, are food preservatives responsible for inhibiting microorganism growth and thus, protecting food products from spoilage. Although these preseratives are recognized by the EFSA and FDA as being safe, there are concerns arising from their wide occurrence in food, cosmetics and pharmaceutical products, that can lead to an increase of the daily intake and possible risks of exceeding the acceptable daily intake (ADI). Therefore, occurrence data are essential to ensure consumer safety through exposure assessment studies. Aim: This study aimed to evaluate the presence of benzoic and sorbic acids in 23 samples of food products commercially available in the market, using a validated HPLC method with UV detection based on European Standard 12856, and compare their levels with the respective allowable limits.